1998
DOI: 10.1074/jbc.273.7.4065
|View full text |Cite
|
Sign up to set email alerts
|

Csk Homologous Kinase, a Novel Signaling Molecule, Directly Associates with the Activated ErbB-2 Receptor in Breast Cancer Cells and Inhibits Their Proliferation

Abstract: Substantial evidence exists supporting direct roles for ErbB-2/neu and Src kinase activation in breast cancer. The Csk homologous kinase (CHK) is a recently identified tyrosine kinase which, like Csk, phosphorylates the C-terminal tyrosine of Src kinases, resulting in inactivation of these enzymes. Recently, we observed that CHK is associated with the ErbB-2/neu receptor upon heregulin stimulation of breast cancer cells. Here, we report that CHK expression was observed in 70 out of 80 primary breast cancer spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…dCSK is more closely related to the human and mouse CSK proteins than any other SFKs ( Figure 2d). Furthermore, as a member of the CSK family, dCSK lacks an N-terminal myristylation site and the C-terminal tyrosine present in other SFKs Okada et al, 1991;Zrihan-Licht et al, 1998). Finally, dCSK specifically phosphorylates the C-terminal tyrosine residue of the Drosophila Src42 protein (Figure 6b).…”
Section: Identification Of Loci That Function With the Lats Tumor Supmentioning
confidence: 99%
See 1 more Smart Citation
“…dCSK is more closely related to the human and mouse CSK proteins than any other SFKs ( Figure 2d). Furthermore, as a member of the CSK family, dCSK lacks an N-terminal myristylation site and the C-terminal tyrosine present in other SFKs Okada et al, 1991;Zrihan-Licht et al, 1998). Finally, dCSK specifically phosphorylates the C-terminal tyrosine residue of the Drosophila Src42 protein (Figure 6b).…”
Section: Identification Of Loci That Function With the Lats Tumor Supmentioning
confidence: 99%
“…There are two members of the CSK family in mammals, CSK and CHK (CSK homologous kinase), which are related to the Src family of tyrosine kinases (SFKs) (Brown and Cooper, 1996; Thomas and Brugge, 1997;Zrihan-Licht et al, 1998;Stamenovic and Coughlin, 1999). Database searches revealed that dCSK is the only CSK homolog in the Drosophila genome.…”
Section: Identification Of Loci That Function With the Lats Tumor Supmentioning
confidence: 99%
“…In normal and cancerous breast cells, Csk is highly expressed and fully active (19). In contrast, Chk is not expressed in normal breast cells, but expression of Chk is induced in breast cancer cells (14). The increased expression level of Chk correlates to suppression of Src, although constitutively expressed Csk fails to suppress Src in these cells (19).…”
mentioning
confidence: 98%
“…To determine whether the similarity in the Chk and Src SH2 domains in binding to Flu-GpYEEI would extend to a physiological phosphopeptide, we synthesized and tested a fluoresceinated phosphopeptide mimicking pTyr 1248 of ErbB2, Flu-NEPEpYLGLDV (FlupY1248) (14,19). This phosphorylation site is responsible for ErbB2 binding to the Chk SH2 domain (14).…”
Section: The Chk and Src Sh2 Domains Have Similar Binding Preferences-mentioning
confidence: 99%
See 1 more Smart Citation